GLOCAREEN–Glocal Character and Environmental Education Based on Madurese Local Wisdom - Suttrisno, Suttrisno; Gunansyah, Genes; Mariana, Neni; Ali, Muhammad Hanif Bin (Studies in Learning and Teaching, 2026)
This study develops a conceptual model of GLOCAREEN, a glocal character and environmental education framework grounded in Madurese local wisdom for primary schools. The study addresses the limited integration between global environmental education frameworks and culturally rooted pedagogical practices in primary education. A conceptual qualitative approach was employed through reflective synthesis and thematic analysis of academic literature published between 2018 and 2025, combined with interpretive analysis of Madurese cultural values such as rokat tase’, gotong royong, and the moral philosophy of ta’ abhenta pote mata and abhenta pote tolang. The findings indicate that glocal education enables the integration of global sustainability principles with local ethical systems, resulting in contextual learning experiences that strengthen students’ ecological awareness and character development. The GLOCAREEN model consists of three core dimensions: global environmental awareness, local cultural embodiment, and hybrid pedagogy. This model contributes theoretically to educational glocalization discourse and pedagogically to the design of contextual environmental learning in primary education.